Social sciences and energy research interactions - Gunes, Umit (ROYAL SOC, 2023)
Energy has had a definitive impact on human life throughout history. Beginning with the harnessing of fire, which offered warmth, improved shelter and more food, humanity's standard of living has been defined by the power derived from fuels and food. Access to energy is the briefest way in which to summarize the history of the world. Direct and indirect causes of war have involved access to energy, and the results of conflicts have been determined by who controlled the energy resources. Therefore, the scientific literature reveals very close interactions between energy studies and social science studies. The Scopus database contains about 118 000 publications in the fields of social sciences and energy. The current study aims to exploit this resource to identify the interactions that exist between the fields so that future research can investigate these more deeply and thus develop solutions to the problems of the modern world. The present article will analyse these publications systematically according to author, country, institution and year, in addition to examining the changes in keywords that have occurred in these studies over the years.This article is part of the theme issue 'Thermodynamics 2.0: Bridging the natural and social sciences (Part 1)'.
Keywords: social sciences; energy research; multidisciplinary; bibliometric analysis; science; interaction; SUSTAINABLE DEVELOPMENT; CITIES; Science & Technology - Other Topics